Spatial variation in tree demography associated to domestic herbivores and topography: Insights from a seeding and planting experiment - Renison, Daniel (2015)
Tropical and subtropical high mountains forests are mainly situated within ravines. Two alternative and often confronted explanations have been proposed for this pattern: that abiotic environmental conditions are favourable for tree establishment only within ravines, or that ravines are less affected by grazing and fires which negatively affect establishment in other sites. Here we propose a mixed explanation and hypothesize that abiotic environmental conditions associated to spatial variation are important during early seedling establishment and that grazing is the main determinant during later stages through its negative effect on survival and growth of larger saplings. We sowed 302,400 seeds and planted 360 saplings of the dominant tree species from the upper Córdoba Mountain range (Central Argentina) with and without grazing in three contrasting sites: a ravine, a valley and a ridge. We monitored seeding plots 5 years until the seedlings reached the height of the planted saplings and we monitored the planted saplings for 12 years. We integrated life stages using matrix multiplications, which resulted in data simulating 17 years of the trees? early development. Our results showed that seedling establishment was lower in the ravine and ridge sites and higher in the valley site with negative differences due to grazing only in the valley. Planted sapling survival increased but growth decreased from ravine to valley and ridge sites in the absence of large herbivores, while both survival and growth were substantially lower in the presence of large herbivores. Matrix multiplications indicated that differences between sites were 5.0 times more important than grazing when integrating up to year 5, but grazing by large herbivores was 5.4 times more important than differences between sites when assessed across the whole 17 year period. We conclude that there could be a strong influence of grazing in restricting high montane forests to sites like ravines where large herbivores are less frequent and show how the relative importance of site characteristics and grazing changes as a result of the length and the differing life stages which are monitored.